Educação especial em Roraima: história, política e memória - Siems-Marcondes, Maria Edith Romano (2013)
This paper studies the historic trajectory of the especial education in the state of Roraima, North of Brazil. It has a Its main objective to understand the processes involves in the formation of this area and investigates the first initiatives on the implementation of the educational services aimed at the people that were considered deficient on learning at the network of public schools in the decade of 1970, until the structuring of a set of schools and assistance services directed at special educations, established within the managing institutions of the state of Roraima until 2001. It describes the historic routes of the actions and policies of the special education in Roraima and its articulation with the national policies in that area. It concerns the research wich was basically built on the dialetic-historic materialism, adopting as its central axis the perspective once introduced by e Edward Palmer Thompson upon a historic analyses that takes by reference the experience of real men and women that, with their living ways, resistances and practiced actions, in several cases apparently passive, build a flow of situations filled with progress, regresses, conflicts and contradictions: I. E., a story seen from the bottom . In this study, the so called a view from the bottom is made up with the catch of the teachers, technicians and family voices involved in the education of the people presenting such deficiencies in Roraima, where those specializes services, regular school spaces count with the direct or indirect presence of the teachers and other specialized professionals. This paper also adopts the voices of these people, among their interviews and reports, as well as among documents daily produced by them, thus originated from institutional activities as a result of such research where we have found the three following development periods: from the beginning of 1970 up until 1983 the moment of the first arisal of the actions taken on the field of the education for these special people; from 1984 up until 1990, in wich such services were officially recognized and fragmented within the special deficiency areas; and from 1991 to 2001, in wich the federal territory became the state of Roraima, and the existence of specific specialized spaces that generated oscillations on the identification of the constitution of the entities wich, sometimes are identified as school space instead of therapeutically spaces. The regional difference, in contrast with other brazilian states, in the fact that all the services are public (governmental, without the presence of any charity or philanthropic entities. This study comes then to the conclusion that it was the geographic isolation and the borderline that made this region, in its late occupation process, be assumed as a national security area, under supervision of the brazilian army in this special case, the air force-, what also turned such area into a field of enforcement of the federal; government's prioritary polices and proposal as a similar attitude of the assumed polices for the educational reforms implemented by the military regime of Brazil from then until today. This situation is yet to be considered even more concrete due to the economical dependency Roraima has from the federal resources whose liberation is conditioned to the implementation of the projects on the preconized ways established by the federal government. It is possible to verify this activity as a natural movement to the pertinent activities of the public services, wich should be maintained and enlarged on their achievement measures and results.